Inverse and Green Logistic: Corporative and Social Environmental University Responsibility, and Productivity - Maquera, Gladys (2012)
Human beings are the cause for the generation of the waste around the world. Dangeroussolid waste represents a meaningful risk to the health just as to the environmental by itscharacteristics and management to which these are submitted. The incentive to the selectivecollection and recycling of the used waste will bring benefits to the society in the energyeconomy of the natural resources generating employment and among others. By the plan,in improving and taking advantage of the natural resources, the inverse Logistic provides theadequate knowledge of the reintegration ways to the marketplace of the benefit goods bythe production process. This work has as main objective in knowing the “Inverse Logistic,”as an option to identify the fundamental aspects that typifying the environmental impact inthe production chain of some resources. At the same time, we present a research work inthe production chain of the petroleum, and consider the production possible cycles as well,if these were implemented by “Inverse Logistic,” technical in the petroleum industry just asin the production of lubricant oil. The correspond work have been performed in four cities ofthe Peru such as: Lima, Juliaca, Puno and Arequipa, where have been visited different publicand privates organizations, which are linked with the petroleum derivatives. In this placeswere observed that generating companies of the wastes do not take awareness neither areresponsible by the final destine of these merely because the legal mark is very few knowingjust as it is incipient. The human kind should understand the God purpose from the creationup to today is the same, and looking the future without forgetting that he is part of Godcreation must reconcile the rest of the creation with Him.